Arqueologia do cotidiano : um flâneur em São Cristóvão - Sergipe - Souza, Fábio Silva (2004)
This dissertation analyses the changing of the public space a long the centuries, having as empiric referring too historic center São Cristóvão town, in Sergipe. This town has politics, historic, archeologic and patrimony important. It appeared in 1590 and it has performed as politics seat of the province until 1855, São Cristóvão was recognized officially since 1938 as monument town of Sergipe Stat. Exempt of the revitalization process, that other historic centers had, this town maintain elements characterized its landscape a long its history. This work landscape a long its history. This work shows as day by day of the social actors, with practice and symbolic disputes, act in sense of the public space formation permitting, then, a multiplicity of its uses, possibiliting the creation territory delimitating at the landscape.